2014
DOI: 10.1016/j.rboe.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of open reduction and internal fixation of severe fractures of the proximal humerus in elderly patients

Abstract: ObjectiveTo evaluate clinical and radiological results with open reduction and internal fixation of severe fractures of the proximal humerus in the patients over the age of 60 years.MethodsBetween June 1992 and February 2011, 21 patients with FGEPU over the age of 60 years were treated by open reduction and internal fixation at the Group of Shoulder and Elbow Department of Orthopaedics and Traumatology of Santa Casa de São Paulo Medical School. 18 patients were reviewed.ResultsTwo patients had excellent result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…Most patients in our study had open reduction and internal fixation procedures performed for both fractures. This is consistent with the findings of prior research, which found that open reduction and internal fixation is the most effective treatment technique for fractures of this kind (Miyazaki et al, 2014;Yuan et al, 2021). Closed reduction, internal fixation, and external fixation were other therapeutic methods.…”
Section: Resultssupporting
confidence: 92%
“…Most patients in our study had open reduction and internal fixation procedures performed for both fractures. This is consistent with the findings of prior research, which found that open reduction and internal fixation is the most effective treatment technique for fractures of this kind (Miyazaki et al, 2014;Yuan et al, 2021). Closed reduction, internal fixation, and external fixation were other therapeutic methods.…”
Section: Resultssupporting
confidence: 92%
“…The Constant-Murley score for the contralateral side was 82.6%, consistent with other studies on nonoperative treatment, 8 11 12 13 14 as well as with the surgical treatment using arthroplasty or locked plate fixation. 17 18 19 20 Subjective scores (i.e., ASES and SANE) were similar to those reported in systematic reviews. 2 Our results reinforce findings from the Proximal Fracture of the Humerus Evaluation by Randomization (PROFHER) study and a Cochrane systematic review demonstrating that nonoperative treatment can provide good functional outcomes even in deviated fractures.…”
Section: Discussionsupporting
confidence: 78%
“…Obtivemos resultados da escala de Constant-Murley relativa ao lado contralateral de 82,6%, valores semelhantes aos de outros estudos sobre tratamento não operatório, 8 11 12 13 14 assim como os obtidos no tratamento cirúrgico com artroplastia ou com a fixação com placa bloqueada. 17 18 19 20 Nas escalas subjetivas, ASES e SANE, obtivemos valores semelhantes ao demonstrado nas revisões sistemáticas. 2 Nossos resultados reforçam os achados do estudo Proximal Fracture of the Humerus Evaluation by Randomization (PROFHER) e da revisão sistemática Cochrane, demonstrando que o tratamento não operatório, mesmo em fraturas desviadas, pode trazer bons resultados funcionais.…”
Section: Discussionunclassified
“…We reviewed various articles and found that many of the articles mentioning severe PHF were based on the Neer classification. 37 - 40 Many 1- or 2-part fractures were treated conservatively. Even with surgical treatment, fixation is easy and robust.…”
Section: Discussionmentioning
confidence: 99%